Mimic: In-situ recording and re-use of demonstrations to support robot teleoperation - MAHADEVAN, Karthik (Institutional Knowledge at Singapore Management University, 2022)
Remote teleoperation is an important robot control method when they cannot operate fully autonomously. Yet, teleoperation presents challenges to effective and full robot utilization: controls are cumbersome, inefficient, and the teleoperator needs to actively attend to the robot and its environment. Inspired by end-user programming, we propose a new interaction paradigm to support robot teleoperation for combinations of repetitive and complex movements. We introduce Mimic, a system that allows teleoperators to demonstrate and save robot trajectories as templates, and re-use them to execute the same action in new situations. Templates can be re-used through (1) macros—parametrized templates assigned to and activated by buttons on the controller, and (2) programs—sequences of parametrized templates that operate autonomously. A user study in a simulated environment showed that after initial set up time, participants completed manipulation tasks faster and more easily compared to traditional direct control.